Design Minkowski Shaped Patch Antenna with Rectangular Parasitic Patch Elements for 5.8 GHz Applications - Hassan, Nornikman; Ahmad, B. H.; Abd Aziz, M. Z. A.; Othman, A. R.; Othman, M. A. (2013)
Abstract—This paper presents the parametric study on the Minkowski shaped antenna with the rectangular parasitic patch elements. This patch antenna consists four parts – patch, feed line, ground plane and parasitic elements. The rectangular parasitic patch elements are located at the bottom of the Minkowski shaped patch. The parametric study of different patch sizes (Design 2A, Design 2B, Design 2C, Design 2D and Design 2E) is presented in this paper. The antenna parameters studied in this paper are resonant frequencies, return loss at the resonant frequency, bandwidth and realized gain. The target frequency of this antenna is 5.80 GHz for Worldwide Interoperability for Microwave Access (WiMAX) application. It shows the return loss of – 24.477 dB, bandwidth of 254 MHz (5.676 GHz to 5.930 GHz) and a gain of 2.351 dB. Index Terms—Minkowski; patch antenna; gain; return loss; bandwidth